Long‐term monitoring shows that drought sensitivity and riparian land use change coincide with freshwater mussel declines - Lopez, Jonathan W.; DuBose, Traci P.; Franzen, Alex J.; Atkinson, Carla L.; Vaughn, Caryn C. (Aquatic conservation, 2022)
Freshwater mussels (Bivalvia: Unionoida) are globally imperilled and are the subjects of wide‐ranging conservation initiatives. This study combined traditional species‐monitoring surveys with a novel functional trait classification scheme and publicly available environmental data to assess potential environmental drivers of declining mussel abundance and species richness. Surveys to document mussel abundance and assemblage composition in south‐east Oklahoma, United States were conducted on the Glover, Mountain Fork and upper Little rivers. Present day survey results (2015–2021) were compared with those from previous studies (1993–1999, 2010) to document long‐term changes in the species and functional composition of mussel assemblages and concurrent changes in climate and land use. Mussel catch per unit effort declined by 71.5% between historical and present day surveys. Species richness declined by 44.4% over this same period. Using a novel classification of mussel drought sensitivity, it was found that the declines were associated with a disproportionate loss of drought‐sensitive taxa (67.0% decline) – those classified as drought‐tolerant did not decline in abundance. Mussel declines coincided with the loss of open surface waters (such as streams, ponds and lakes) and riparian wetlands, increased local air temperatures and longer and more intense hydrological drought. These findings indicate that for a complete understanding of the causes and consequences of mussel declines, conservation biologists must not only monitor the species composition and abundance of threatened organisms, but also consider functional traits. The results further underscore the importance of long‐term monitoring for long‐lived organisms owing to the decadal time scales over which climate and land use change occur.